Pengelolaan Nilai Tunai Dalam Surplus Underwriting Di Agen Rinto Prudential Syariah Wonosobo - Fatmawati, Fatmawati (Program Studi Hukum Ekonomi Syariah, 2022)
Sharia insurance is one of the products of Islamic Financial Institutions that currently exist among the public today. However, limited public knowledge often causes misunderstandings between the community and insurance participants so that many of them think they are losing money when investing their money for insurance. Whereas in reality, those who invest their funds in insurance products actually get two benefits at once, namely insurance coverage benefits and long-term investment benefits. Therefore, before buying an insurance product, it is necessary to learn more about what insurance product to buy and how to manage the investment. Is the product purchased in accordance with the provisions of the Shari'a or not. Here the author provides an overview of several life insurance products at Prudential Syariah Wonosobo related to investment in more detail. This study uses a field research method where the author conducts research and collects data directly to the research location with qualitative data analysis methods. The results of this study indicate that based on the source of funds and their management, the cash value in this underwriting surplus is in accordance with the theories and concepts in fiqh muamalah, free from elements of usury, gharar and maisir. A clear separation of funds and profit sharing is the hallmark of this sharia insurance.